1992
DOI: 10.1021/jm00082a014
|View full text |Cite
|
Sign up to set email alerts
|

Binding of phenylalkylamine derivatives at 5-HT1C and 5-HT2 serotonin receptors: evidence for a lack of selectivity

Abstract: Certain phenylalkylamine derivatives have been considered to bind selectively at 5-HT2 serotonin receptors. It is now recognized that the most widely used derivatives, i.e., 1-(2,5-dimethoxy-4-X-phenyl)-2-aminopropanes where X = Me (DOM), Br (DOB), and I (DOI) (1-3, respectively) also bind at the more recently identified population of serotonin 5-HT1C receptors. The purpose of the present investigation was to determine whether simple phenylalkylamines bind selectively at one population of receptors over the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
0
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 0 publications
3
83
0
5
Order By: Relevance
“…Among the best known are 2,5-dimethoxy-4-iodophenethylamine (2C-I), 2,5-dimethoxy-4-bromophenethylamine (2C-B), and 2,5-dimethoxy-4-methylphenethylamine (2C-D), the ␣-demethylated analogs of DOI, DOB, and DOM, respectively. The data available for these phenethylamines show that their affinities for 5-HT 2A receptors are similar to those of their phenylisopropylamine counterparts, whereas different functional models have shown that their efficacies are lower than those of their ␣-methylated analogs (Glennon et al, 1992;Nichols et al, 1994;Acuñ a-Castillo et al, 2002;Parrish et al, 2005). Again, with few exceptions, most in vitro studies on these compounds examined only PLC-mediated responses.…”
mentioning
confidence: 99%
“…Among the best known are 2,5-dimethoxy-4-iodophenethylamine (2C-I), 2,5-dimethoxy-4-bromophenethylamine (2C-B), and 2,5-dimethoxy-4-methylphenethylamine (2C-D), the ␣-demethylated analogs of DOI, DOB, and DOM, respectively. The data available for these phenethylamines show that their affinities for 5-HT 2A receptors are similar to those of their phenylisopropylamine counterparts, whereas different functional models have shown that their efficacies are lower than those of their ␣-methylated analogs (Glennon et al, 1992;Nichols et al, 1994;Acuñ a-Castillo et al, 2002;Parrish et al, 2005). Again, with few exceptions, most in vitro studies on these compounds examined only PLC-mediated responses.…”
mentioning
confidence: 99%
“…This compound is equipotent as a releaser of dopamine, norepinephrine and 5-HT [4], It also shows low affinity for 5-HT 2 receptors [15]. However, with respect to 5-HT release, 4-MA was significantly more potent compared to amphetamine [4].…”
Section: Discussionmentioning
confidence: 99%
“…In present experiments, when animals were pre-treated with ketanserin or haloperidol (at doses that did not affect basal locomotor activity), the hyperlocomotion of 4-MA was partially inhibited, suggesting both 5-HT and dopamine take part in this effect. According to previously published studies [15] The main problem associated to 4-MA exposure is the acute toxicity of this drug, which seems to be linked to hyperthermia. For this reason, we focused our attention on the effects of 4-MA on body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Many drugs with agonist properties at 5-HT2A receptors also have agonist properties at 5-HT2C and other receptor subtypes; this is clearly the case with LSD (Marek and Aghajanian 1996), DOM (Glennon et al 1992), and DMT (Smith et al 1998). Therefore, it is difficult to attribute the behavioral or neurotoxic effects of these compounds exclusively to their actions at the 5-HT2A receptor.…”
Section: Discussionmentioning
confidence: 99%